(untitled) (Educational Dimension, 2020)
The mind maps that students compile are subject to verification. To compare graphs, you need to develop an application that connects to the control system training on the server. To reduce the complexity of application development, you need to limit the choice of texts added by students to the knowledge map, the choice of terms from the thesaurus subject area. Automatic assessment of the quality of intelligence maps created by students when mastering the topics of the course can be performed in this way. The restrictions imposed to solve this problem are the prohibition of entering texts from the keyboard. Signatures to card nodes must be selected from a list prepared in advance — from terminological dictionary of the subject area. The need to limit text input requires abandoning the use of common programs and online services for building smart maps. In fact, it is necessary develop new software or modify one of the existing software packages available under an open source license. Perhaps, for the first iterations it is necessary to be limited only to text representation of a card in the outline mode as it is implemented in text2mindmap service.